2019
DOI: 10.31031/mcda.2019.03.000572
|View full text |Cite
|
Sign up to set email alerts
|

Use of Seagrasses as Natural Forage Source for Small Ruminants: The Example of the Marine Plant Posidonia oceanica

Abstract: The search for new sources of food that contribute to the optimization of livestock production is urgently needed, especially in the Spanish SE where rainfall is increasingly scarce and land degradation makes grazing of small ruminants difficult. This work provides in vivo and in vitro data on the nutritional composition, digestibility, inputs in sheep and goats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 15 publications
4
1
0
Order By: Relevance
“…Indeed, it appears incorporation of this seagrass as an alternative fiber source to oat hay improved goat mammary health status. Similar findings were reported by Castillo et al (2015Castillo et al ( , 2019 who observed significant decreases in SCC in Murciano-Granadina goats fed P. oceanica. These authors explained this phenomenon by the high content of secondary metabolites in P. oceanica, mainly phenolic compounds and flavonoids, known for their defensive and antioxidant properties, which can significantly reduce the occurrence of udder infections.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Indeed, it appears incorporation of this seagrass as an alternative fiber source to oat hay improved goat mammary health status. Similar findings were reported by Castillo et al (2015Castillo et al ( , 2019 who observed significant decreases in SCC in Murciano-Granadina goats fed P. oceanica. These authors explained this phenomenon by the high content of secondary metabolites in P. oceanica, mainly phenolic compounds and flavonoids, known for their defensive and antioxidant properties, which can significantly reduce the occurrence of udder infections.…”
Section: Discussionsupporting
confidence: 90%
“…According to Eldik et al (2017), complete substitution of barley straw by P. oceanica showed no significant effect on milk production in Murciano-Granadina goats. Similar results were reported by Castillo et al ( , 2019, demonstrating that Murciano-Granadina goats can be fed dried P. oceanica as a source of fiber at levels up to 450 g/d without affecting milk production. Using P. oceanica as partial or total substitute for oat hay significantly improved fat content in goat's milk.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations